1978
DOI: 10.1002/bbpc.197800010
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the Structure of Laminar Flat Flames I: Flame Velocity of Freely Propagating Ozone Decomposition Flames

Abstract: A method is described which allows to include complete multicomponent formulation of diffusion and heat conduction in the solution of the time‐dependent conservation equations of a laminar flat flame. Calculations with simplified transport models are presented for comparison. — For the ozone decomposition flame this method is used for the determination of the flame velocity of freely propagating flames as a function of the initial ozone oxygen ratio. There is agreement with experimental values. Discrepancies b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Grotheer and Keirn (1989) have recently conducted a detailed numerical study of methanol flames with the latest information of Norton andDryer (1989) andTsang (1987), predicting laminar flame speeds of methanol/air mixtures at p = I atm and T" = 298 K conditions. In this study, the one-dimensional, time-dependent flame code of Warnatz (1978) was used and a number of revisions was adopted due to significant overprediction of the flame speeds of rich mixtures. The revised scheme was tested against our experimental data for stoichiometric flames at various initial temperatures using the Sandia flame code (Kee et al, 1985;Grear et al, 1986), and the results are shown in Figure II.…”
Section: Chcomentioning
confidence: 99%
“…Grotheer and Keirn (1989) have recently conducted a detailed numerical study of methanol flames with the latest information of Norton andDryer (1989) andTsang (1987), predicting laminar flame speeds of methanol/air mixtures at p = I atm and T" = 298 K conditions. In this study, the one-dimensional, time-dependent flame code of Warnatz (1978) was used and a number of revisions was adopted due to significant overprediction of the flame speeds of rich mixtures. The revised scheme was tested against our experimental data for stoichiometric flames at various initial temperatures using the Sandia flame code (Kee et al, 1985;Grear et al, 1986), and the results are shown in Figure II.…”
Section: Chcomentioning
confidence: 99%
“…Due to this fact, and since our time integration procedure is still fully explicit, we restrict ourselves in this ÿrst study to ozone ames. It is well known that the chemical processes (Table I) controlling ozone decomposition [45] show very slow characteristic chemical times.…”
Section: Structure Of a Turbulent Ozone Amementioning
confidence: 99%
“…24 Warnatz has studied extensively both freely propagating and burnerstabilized flames in a variety of premixed gases. 25 "" 29 He linearizes the chemical reaction terms and solves the time-dependent equations implicitly with assumed initial guesses for the temperature and species profiles. He also uses a simplified transport model 25 that agrees well with the complete multicomponent formulation of diffusion and thermal conduction.…”
Section: Modeling Of Laminar Flamesmentioning
confidence: 99%